2017
DOI: 10.1177/1352458517720044
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in multiple sclerosis: Frequency and clinical relevance of anti-drug antibodies

Abstract: Rituximab treatment is associated with a high degree of ADAs, which correlates with efficacy of B-cell depletion; however, the clinical relevance of ADAs remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 19 publications
5
71
0
2
Order By: Relevance
“…However, although the presence of ADAs was associated with incomplete B cell depletion, no relationship could be established with adverse events or patient outcomes. 211 Accordingly, it remains unclear how important an issue ADAs are for anti-CD20 mAbs, and further study is required to clarifiy the significance of this phenomenon.…”
Section: Anti-drug Antibodiesmentioning
confidence: 99%
“…However, although the presence of ADAs was associated with incomplete B cell depletion, no relationship could be established with adverse events or patient outcomes. 211 Accordingly, it remains unclear how important an issue ADAs are for anti-CD20 mAbs, and further study is required to clarifiy the significance of this phenomenon.…”
Section: Anti-drug Antibodiesmentioning
confidence: 99%
“…The therapeutic use of monoclonal antibodies and other biopharmaceutical products can result in an immune response to the drug that, in some cases, affects its efficacy due to the production of neutralizing ADAs 5 . Several clinical studies have measured ADA levels in sera of selected cohorts of patients and concluded that not all antibody responses lead to drug neutralization [6][7][8][9][10][11] . However, an explanation for these heterogeneous responses and an integrated characterization of the B and T cell responses to the drug are still missing.…”
mentioning
confidence: 99%
“…In our case, it may be a coincidence that this very patient did not experience any CWD or relapses while on RTX. However, in a cross‐sectional study by Dunn et al, samples were collected from 339 RTX‐treated subjects with MS to determine the clinical relevance of ADA. The authors showed that RTX was associated with a high degree of ADA, which in turn correlated significantly with incomplete B‐cell depletion.…”
Section: Discussionmentioning
confidence: 99%